THE CURRENT CIRCUMSTANCES AND CHALLENGES OF MIGRANT LABOR FORCE OF MONGOLIA IN NORTH EASTERN ASIA - Altanchimeg, Z; Battuya, D; Tungalag, J (SCAD Independent, 2016)
The current study addressed the current circumstances and challenging issues for the Mongolian migrants. We involved in the survey citizens who have been lived and worked in the Republic of South Korea and Japan. According to the results of the survey, working of Mongolian citizens in hazardous and insecure working conditions reveals the weak coherence between regulation and policies towards to the immigration and professional organizations. We concluded that one of the priorities in the area should be developing a sound policy on migrant labor force that meets international labor standard with considering of economic, social policies and then in the implementation process establishing centralized database is crucial.